Changes in EBV Association Pattern in Pediatric Classic Hodgkin Lymphoma From a Single Institution in Argentina - De Matteo, Elena; García Lombardi, Mercedes; Preciado, Maria V.; Chabay, Paola (Frontiers in Oncology, 2019)
In Classic Hodgkin lymphoma (cHL), Epstein Barr virus (EBV) association varies worldwide. Aims: Our aim was to analyze EBV-association with pediatric cHL for the last 28 years. Methods: EBV presence was evaluated by EBERs in situ hybridization, and LMP1 immunohistochemistry. Results: Until 2008, we found in pediatric cHL a similar percentage of EBV presence to those observed in adult cHL from developed populations. Nevertheless, in the last 8 years, an unexpected difference in cHL EBV association was proven, along with a slight bias of EBV association with the nodular sclerosis (NS) subtype. Concerning histological subtype distribution, even though MC still prevailed in the whole series, those cases diagnosed as NS showed a sustained rise from 1989 until today. Conclusion: Variations of EBV association of cHL related to geography, age, ethnicity, and histological type have been largely described when compared different world regions, but interestingly this single center revised series brought to light the dynamic process behind the evolution of this relationship over time.